Tango with nature [videorecording] the Taiwan story of sustainable development. (Kwang Hwa Mass Communication, 2004)
From the 16th century onwards, Taiwan was known to the West as Ilha Formosa (Beautifu Island in Protuguese). The island's beauty stems from inhabitants' close interaction with the environment, their "tango nature." The hunting taboos established by their ancestors enabled Taiwan's indigenous peoples to coexist with nature. The island's inhabitants respected the workings of nature and lived, worked and rested in accordance with the seasons. Even with today's commercial and indutrial developments that have made Taiwan a highly-developed society, its people still strive to balance economic development with environment protection. This will allow them to reap the benefits of a competitive technology-based economy without losing the enjoyment of the island's mountains and forest.